Factors that influence the response time in STEMI patients in Lisbon 2017. (30th September 2020) - Gil, M; Garcia, M; Aguiar, P
Abstract: The success of the ST-segment elevation myocardial infarction (STEMI) approach is based on early diagnosis and on the institution of timely reperfusion therapy, with response times remaining variable. The objective of this study was to determine which factors influenced the response time to patients with STEMI until the treatment with coronary reperfusion from the prehospital service or the emergency room in three hospitals in the greater Lisbon area in 2017. An epidemiological, cross-sectional, retrospective, descriptive study with an analytical component was performed, with data from the National Institute of Medical Emergency (INEM) and clinical trials of patients. Patients who were not referred to these hospitals were excluded. Univariate statistical analysis was performed, as well as c2 tests, t-student and logistic regression model (r < 0.05). The population included 95 patients, the majority being male (67.4%), and with a mean age of 63.8 years. 61.1% were hypertensive and the majority (87.4%) had no signs of previous heart failure. The mean door-to-balloon time was 159 minutes, with 57.4% showing time greater than 120 minutes. In patients in whom the INEM Coronary Greenway was activated, mean door-to-balloon time was 99 minutes. Diagnostic, symptom-admission and transport times showed a statistically significant association with the door-to-balloon time in the bivariate analysis. The times are fulfilled in the prehospital service, but in the hospital, services can be improved through the early accomplishment of electrocardiogram and the optimization of interhospital transport. Key messages: Reducing ECG time and inter-hospital transport time improves STEMI response and outcome. Time is muscle is the main message for de concern of identifying influence factors of STEMI response time.